MEMPERKENALKAN DAN MENUMBUHKAN MINAT WARGA DENGAN BERWIRAUSAHA MINUMAN EMPON-EMPON - Lustia Husnul Khofifah; Husnul Khatimah; Purnama Putra (Universitas Islam 45 Bekasi, 2022)
Real Work Lecture (KKN) is a student service activity to the community that is carried out in an area. This activity is one of the subjects that must be taken by UNISMA students, KKN is also a form of student service through empowerment, training, counseling, mentoring, mentoring and to explore the potential that can be developed by the community. Based on this goal, the deployment of KKN students is expected to help the residents of Kranji Village, West Bekasi. There are 2 programs, namely the mandatory program (Supporting the prevention of violence and sexual harassment) and the elective program (introducing and growing people's interest in the Empon-empon beverage entrepreneurship). It is hoped that the local residents, especially teenagers and young mothers, can use their time to be more useful in terms of entrepreneurship and increase their knowledge in terms of preventing sexual harassment.